THE EFFECT OF USING VIDEO ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Samuel N Panjaitan; Sri Juriati Ownie (Universitas Negeri Medan, 2015)
The objective of the study was to investigate if using video significantly affectedstudents’ achievement in writing procedure text. This study was conducted byexperimental research. The population of the study was all the students of gradeIX of SMP Negeri 5 Sipahutar with the total number of the students was 96 inclasses. There were 64 students chosen as the sample by using random samplingtechnique. The sample was divided into two groups, namely control group andexperimental group. The experimental group was taught by using video andcontrol group was taught without using video. The instrument for collecting datawas writing test. To obtain the reliability of the test, the writer applied PearsonProduct Formula. The calculation showed that the reliability of the test is 0.87. Itwas categorized very high reliability. The data were analyzed by using t-testformula. The result of analysis shows that t-observed value is higher than t table(3.50>2.00) at level of significance 0.05 the degree of freedom 62. It means thatthe alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected.Based on the findings of this study, it found that there is a significant effect ofusing video on students’ achievement in writing procedure text.